Depression score mediate the association between a body shape index and infertility in overweight and obesity females, NHANES 2013–2018 - Qiangwei Pan; Xiaolu Shen; Hongfeng Li; Bo Zhu; Dake Chen; Jiajia Pan (BMC Women's Health, 2023)
Abstract Background Overweight and obese females demonstrate a significantly increased risk of anovulatory infertility. This study aims to investigate whether depression score could mediate the association between a body shape index (ABSI) and infertility, especially in overweight and obese population. Methods We included 5431 adult female Americans from the National Health and Nutrition Examination Survey (NHANES, 2013–2018) database. ABSI manifested the body shape using waist circumference, weight, and height. Infertility or fertility status was defined by interviewing female participants aged ≥ 18 through the reproductive health questionnaires. Depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9) with total scores between 0 and 27. To investigate the association of infertility with ABSI and other individual components, survey-weighted multivariable logistic regression was performed. Mediation analysis of PHQ-9 score was conducted to disentangle the pathways that link ABSI to infertility among the NHANES participants. Results 596 (10.97%) females were categorized with having infertility among 5431 participants. Participants with infertility showed higher ABSI and PHQ-9 score, appearing greater population proportion with depression symptoms. In the multivariable logistic regression model, ABSI (adjusted odds ratio = 0.14, 95% CI: 0.04 to 0.50) and PHQ-9 (adjusted odds ratio = 1.04, 95% CI: 1.01 to 1.07) were positively associated with infertility. PHQ-9 score was estimated to mediate 0.2% (P = 0.03) of the link between ABSI and infertility in all individuals, but to mediate 13.5% (P < 0.01) of the ABSI-infertility association in overweight and obese adult females. Conclusion The association between ABSI and infertility seems to be mediated by depression symptoms scored by PHQ-9, especially in those adult females with overweigh and obesity. Future studies should be implemented to further explore this mediator in ABSI-infertility link.